FAKTOR RISIKO KEJADIAN CAMPAK DI DESA TENGARAN, KECAMATAN TENGARAN, KABUPATEN SEMARANG, JAWA TENGAH - Ambar Yuniarti, Retno (Jurnal Kedokteran YARSI, 2007)
A risk factor study of measles was conducted at Tengaran Village, Tengaran Sub district, Semarang Regency, Central Java. The aim of the study was to describe distribution and risk factors of measles on the children under 15 years old. The study design was a case control study, and the data was collected retrospectively. The interview was conducted with respondents by questionnaire. Sample size was calculated using Fleiss formula for unmatched case control study employing a soft ware Epi info 6.1 program with 95% confidence limits, 80% power test and 0.05 a error. Subjects in this study were 73 for cases and 105 for control. The results showed that the immunization status had a significant correlation with measles cases (p 0.05). Nutrition status had no significant correlation with measles cases (p 0.05). House  condition had a significant correlation with measles cases (p 0.05), but had no significant correlation with nutrition status (p 0.05). The education and income factor had no significant correlation with nutrition status (p 0.05). Nevertheless, significant correlation was observed between education factor and immunization status  (p 0.05).